Physiologic Variability of Single-Voxel Proton MR Spectroscopic Measurements at 3T - Wellard, R. Mark (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: Physiologic and scanner variability of proton MR spectroscopy (MRS) measurements can limit the detection of subtle metabolite fluctuations. We assessed the variability of such measurements at 3T and compared two methods to obtain absolute concentrations. METHODS: Variability over 14 days was assessed with short-echo, single-voxel proton MRS in 14 control subjects and in a phantom containing 50 mmol/L N-acetylaspartate (NAA). Spectra were analyzed by using LCModel, scaling factors determined with both the calibration phantom (CP), and water peak intensity (WP) methods. Relative (reflecting the systematic drift) and absolute variability (reflecting the magnitude of scanner variability) was determined. RESULTS: For the phantom, initial (49 ± 1.7 mmol/L) and second measurements (50 ± 1.6 mmol/L) showed similar results, with small variability (relative, −0.6 ± 1.5 mmol/L; absolute, 1.1 ± 1.1 mmol/L). Control subjects had no systematic difference between the two scans for any measurement. Absolute variabilities in the temporal lobe for total NAA (NAA+NAAG) were 13% (CP) and 11% (WP). The largest variability (29%) was found for glutamate-glutamine (29%) with the CP method, and for myo-inositol with the WP method (28%). Absolute variability was smaller for the frontal lobe measurements (total NAA 7% and overall 6–18% for CP; total NAA 6% and overall 5–19% for WP). No significant difference was observed between the two methods. CONCLUSION: Physiologic variability is the major source of measurement variability and accounts for 12% of the variability in temporal lobe total NAA. Therefore, total NAA variations must clearly exceed this before they can reliably be attributed to an effect of disease.